ANALISA PENJADWALAN WAKTU PEMBANGUNAN LANJUTAN SMPN 38 LOK BAHU KOTA SAMARINDA - CHANG, KELVIN (KURVA S JURNAL MAHASISWA, 2018)
Since 2012, students of 38 Lok Bahu Junior High School must have a place at 027 Samarinda Elementary School. This was caused by the lack of funds from the Samarinda city government. However, it seems that the students of 38 Lok Bahu Junior High School can breathe a sigh of relief, because in mid 2018 the construction of the school which had stopped would be resumed. For this reason, the contractor in the implementation must be done well. Considering the previous project, the contractor appointed as the executor of this project advanced development project experienced delays in the realization of the project. This study will analyze the scheduling of time related to the optimal duration, critical trajectories and work networks that can be made in the advanced development activities of 38 Lok Bahu Junior High School using the CPM method, PERT and using Microsoft Project software. In the CPM method, the settlement time is around 266 days, while in PERT method, it is obtained 179 days of completion (June 2 - December 8, 2018), faster than 1 day from the plan schedule. Therefore, 179 days duration can be said as the optimal duration. The completion time with CPM and PERT methods is 87 days different. This is because the duration of activities in the PERT method obtained from interviews with the foreman, the duration is shorter or relatively fast than the plan, especially in supporting concrete structure work. Based on the calculations that have been made, the probability of project completion at 179 days is around 55.19%. The critical path in this project is A (Preliminary Work) - B (Supporting Concrete Structural Work) - C (Pair of Brick and Plaster) - D (Floor Work And Ceramic Wall) - F (Roof Frame Work) - G (Cover Wood And Ceiling Works) - H (Electrical And Mechanical) - K (Other Work).